Gut microbial composition difference between pediatric ALL survivors and siblings. (17th August 2020) - Thomas, Ronay; Wong, Wendy S. W.; Saadon, Reem; Vilboux, Thierry; Deeken, John; Niederhuber, John; Hourigan, Suchitra K.; Yang, Elizabeth
Abstract: Acute lymphoblastic leukemia (ALL) is the most common childhood cancer with high cure rates leading to rising numbers of long-term survivors. Adult survivors of childhood ALL are at increased risk of obesity, cardiovascular disease, and other chronic illnesses. We hypothesize that ALL therapy is associated with long-term gut microbiome alterations that contribute to predisposition to chronic medical conditions. We conducted a pilot study to test whether differences can be detected between stool microbiota of pediatric ALL survivors and their siblings. Stool samples were collected from 38 individuals under age 19 who were at least 1 year after completion of therapy for ALL. Stool samples collected from 16 healthy siblings served as controls. 16S ribosomal RNA gene sequencing was performed on the stool samples. Comparing microbiota of survivors to sibling controls, no statistically significant differences were found in alpha or beta diversity. However, among the top 10 operational taxonomic units (OTUs) from component 1 in sparse partial least squares discriminant analysis (sPLS-DA) with different relative abundance in survivors versus siblings, OTUs mapping to the genus Faecalibacterium were depleted in survivors. Differences in gut microbial composition were found between pediatric survivors of childhood ALL and their siblings. Specifically, the protective Faecalibacterium is depleted in survivors, which is reminiscent of gut microbiota alteration found in adult survivors of childhood ALL and reported in obesity, suggesting that microbiota alterations in pediatric ALL survivors start in childhood and may play a role in predisposition to chronic illness in later years of survivorship.